Agricultural exposures to carbamate herbicides and fungicides and central nervous system tumour incidence in the cohort AGRICAN. (September 2019) - ,; Arveux, P.; Bara, S.; Bouvier, A.M.; Busquet, T.; Colonna, M.; Coureau, G.; Delanoé, M.; Grosclaude, P.; Guizard, A.V.; Herbrecht, P.; Laplante, J.J.; et al.
Abstract: Background: Pesticides exposures could be implicated in the excess of Central Nervous System (CNS) tumors observed in farmers, but evidence concerning individual pesticides remains limited. Carbamate derivative pesticides, including herbicides and fungicides ( i . e . (thio/dithio)-carbamates), have shown evidence of carcinogenicity in experimental studies in animals. In the French AGRICAN cohort, we assessed the associations between potential exposures to carbamate herbicides and fungicides and the incidence of CNS tumors, overall and by histological subtype. Methods: AGRICAN enrolled 181, 842 participants involved in agriculture. Incident CNS tumors were identified by linkage with cancer registries from enrollment (2005–2007) until 2013. Individual exposures were assessed by combining information on lifetime periods of pesticide use on crops and the French crop-exposure matrix PESTIMAT, for each of the 14 carbamate and thiocarbamate herbicides and the 16 carbamate and dithiocarbamate fungicides registered in France since 1950. Associations were estimated using proportional hazard models with age as the underlying timescale, adjusting for gender, educational level and smoking. Results: During an average follow-up of 6.9 years, 381 incident cases of CNS tumors occurred, including 164 gliomas and 134 meningiomas. Analyses showed increased risks of CNS tumors with overall exposure to carbamate fungicides (Hazard Ratio, HR = 1.88; 95% CI: 1.27–2.79) and, to a lesser extent, to carbamate herbicides (HR = 1.44; 95% CI: 0.94–2.22). Positive associations were observed with specific carbamates, including some fungicides (mancozeb, maneb, metiram) and herbicides (chlorpropham, propham, diallate) already suspected of being carcinogens in humans. Conclusions: Although some associations need to be corroborate in further studies and should be interpreted cautiously, these findings provide additional carcinogenicity evidence for several carbamate fungicides and herbicides. Highlights: Findings reinforce evidence of carcinogenicity in humans for some (thio/dithio)-carbamate herbicides and fungicides that were already suspected of being carcinogens. Findings show two to three times higher CNS tumor risks following exposure to the (dithio/thio)-carbamates used by farmers growing vineyards, fruits, potatoes and beets. The majority of studied active ingredients are no longer marketed in 2018, but some are still on the European market, and others were registered too recently to be studied.